What's at Stake in the Race Debate?. (30th July 2022) - Mallon, Ron
Abstract: How can there be so much apparent disagreement about what race is, when there is so much agreement on the facts surrounding race? In this paper, I develop this puzzle and consider several interpretations of work in the philosophy of race to try to answer it, several ways of understanding what the metaphysics of race is doing. I consider and reject the possibility that apparent disagreement is metaphysically substantive, and I also consider and reject the view that apparent disagreement primarily reflects semantic disagreements. Instead, I suggest that apparent first‐order disagreement over the existence and character of race is a part of a broader, metalinguistic negotiation or conversation about how racial terms can or ought to be used, and I note a range of considerations—including semantic, pragmatic, epistemic, and ethical—that properly play a role in this discussion.